2020
DOI: 10.1101/2020.11.23.391474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local brassinosteroid biosynthesis enables optimal root growth

Abstract: Brassinosteroid hormones are indispensable for root growth and they control both cell division and cell elongation through the establishment of an increasing signaling gradient along the longitudinal root axis. Because of their limited mobility, the importance of brassinosteroid distribution for achieving the signaling maximum is largely overlooked. Expression pattern analysis of all known brassinosteroid biosynthetic enzymes revealed that not all cells in the Arabidopsis thaliana root possess full biosyntheti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…A recent study reported Article that BR biosynthetic enzymes exhibited different expression patterns in the Arabidopsis root and that BR intermediates need to be exchanged between neighboring cells for conversion to bioactive molecules. 33 It is possible that the completion of BR biosynthesis in ovules also relies on the cell-to-cell movement of BR precursors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported Article that BR biosynthetic enzymes exhibited different expression patterns in the Arabidopsis root and that BR intermediates need to be exchanged between neighboring cells for conversion to bioactive molecules. 33 It is possible that the completion of BR biosynthesis in ovules also relies on the cell-to-cell movement of BR precursors.…”
Section: Discussionmentioning
confidence: 99%
“…42 The same methods were used for generating KNU pro :BEH1, KNU pro :WRKY23 and BZR1 pro :WRKY23 constructs. Promoter-3xVENUS-N7 (for BRbiosynthetic genes and BEH2/3) were generated by amplifying 2 kbp upstream of the BR-biosynthetic genes, which have been shown to be fully functional, 33 and BEH2/3 genes sequences from wild-type genomic DNA using primers listed in Table S1. PCR fragments were cloned into the SPL4 pro :3xVENUS-N7 vector using BamHI and XbaI restriction sites.…”
Section: Article Plasmid Constructionmentioning
confidence: 99%
“…Patterning of hormonal signals along root developmental axis is critical for optimal root growth and development. Local BR biosynthesis has been shown to peak in the elongation zone [ 33 ], coinciding with the optimal onset of cell elongation in the transition zone located between the meristem and elongation zone. As a result, exogenous BR or PPZ treatment may not promote optimal root elongation due to unbalanced activity in the meristem and elongation zone.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, whole microscope bodies have been printed, including the base (13,15), the body (13,15,16), holders for the filters (15,17), objectives (18), coverslips (14), pinholes (14,16) and heat sinks (18). Additionally, microscope chambers (19) and controller mounts (20) have also been implemented, allowing a high degree of customisation to researchers that adopt this technology. 3D printing is also used to print tools that allow for more complex microscopy solutions.…”
Section: D Printing In Microscopymentioning
confidence: 99%